THE SEMITIZATION OF ITIHASA: INTERTEXTUALITY OF THE MAHABHARATA AND THE RAMAYANA IN THE JUDAEOÂâ€ISLAMIC TEXTS - Ali, Mochammad (Balai Bahasa Jawa Timur, 2013)
Abstract: This article is an intertextual study of Judaeo?Islamic texts with the Itihasa. This research explores the discourse of Semitic and Aryan texts already canonized in cultural artifacts of Abrahamic and Brahmanic traditions which require a parallelization of substantive messages. It is not only depending on comparative linguistic similarities but also referring to the common theological formula surrounding the text in a chain of traditions which created the text. The text cannot be regarded as an independent text but have to be understood through the process of ?reading? in a context that can be ascertained to have a close relationship with other texts. It exists as a weave of discourses which are surrounding the text through the process of adoption, adaptation, and reformulation of the text that has been established in the context of a sequence of tradition inheritance. The study of cultural semiotics readable through the text is not intended to vulgarly expose the text that deviates from the hiperreality context of the text an sich. Instead, it aims to explain the ?marker? in the text across boundaries of times, geographies, languages, and common traditions through the system of transmission. This article uses a semiotic theory proposed by Julia Kristeva. Abstrak: Tulisan ini merupakan studi intertekstualitas teks Judaeo?Islam dengan teks Itihasa. Penelitian ini mengeksplorasi wacana teks rumpun Semit dan Arya yang terekam dalam artefak kebudayaan bertradisi Abrahamik dan Brahmanik yang meniscayakan pararelisasi pesan substantif. Pararelisasi pesan tidak hanya berpijak pada latar similaritas linguistik tetapi juga merujuk pada kesejajaran formula teologis yang melingkupi teks dalam rentetan tradisi yang melahirkan teksnya. Teks tidak dapat dipandang sebagai sebuah teks yang independen, tetapi harus dipahami melalui proses ?pembacaan? dalam konteksnya yang dapat dipastikan berkaitan erat dengan teks liyan. Teks hadir sebagai sebuah tenunan wacana yang melingkupi penjadian teks melalui proses adopsi, adaptasi, maupun reformulasi teks yang telah mapan dalam konteks rangkaian pewarisan tradisi. Kajian semiotika kultural yang terbaca tidak dimaksudkan untuk menelanjangi wacana teks secara vulgar yang teralienasi dari konteks hiperealitas teksnya, tetapi bertujuan untuk menjelaskan ?penanda? dalam teks yang melintas batas zaman, geografis, bahasa, maupun tradisi serumpun melalui sistem transmisinya. Artikel ini menggunakan teori semiotik yang dikemukakan oleh Julia Kristeva. Kata-kata kunci: intertekstualitas; Ramayana; Mahabharata; Semit; Arya